Collateral Channel Size and Tortuosity Predict Retrograde Percutaneous Coronary Intervention Success for Chronic Total Occlusion. (January 2018) - Huang, Ching-Chang; Lee, Chih-Kuo; Meng, Shih-Wei; Hung, Chi-Sheng; Chen, Ying-Hsien; Lin, Mao-Shin; Yeh, Chih-Fan; Kao, Hsien-Li
Abstract : Background—: There is little evidence on how to select an interventional collateral channel (CC) in retrograde chronic total occlusion (CTO) percutaneous coronary intervention. We aimed to identify independent angiographic predictors of CC tracking and technical success in retrograde CTO percutaneous coronary intervention. Methods and Results—: From January 2012 to December 2015, a total of 216 consecutive retrograde CTO percutaneous coronary intervention attempts by a high-volume operator in a tertiary university-affiliated hospital were enrolled. The clinical, angiographic, and procedural details were collected. The characteristics analyzed included channel type, size, tortuosity, angle of attack, length to emerging point, and the Multicenter CTO Registry of Japan score. The Multicenter CTO Registry of Japan score was 4.2±0.8. A total of 242 CCs were attempted for intervention. CC tracking success rate was 83.5%, and the technical success rate (per CC) was 81.4%. The per-patient technical success rate was 91.2%, and the major procedural complication rate was 4.6%. The atrioventricular groove, epicardial, and septal CCs were used in 36 (14.9%), 84 (34.7%), and 122 (50.4%) tracking attempts, respectively. In multivariable analysis, only large channel size and lack of tortuosity were significant independent predictors of CC tracking and technical success. A new scoring system was developed, while large size was given 1 point and lack of tortuosity was given 2 points. The receiver-operating characteristic area by the new model to predict CC tracking and technical success were 0.800 and 0.752, respectively. Conclusions—: In retrograde CTO percutaneous coronary intervention, only size and tortuosity of a CC are independent angiographic predictors of CC tracking and technical success.